Towards Sustainable Excellence: Exploring The Synergy Of Ambidextrous Sustainability And Sustainability Risk Management - Robby Krisyadi; Yolanda Masnita; Husna Leila Yusran; Teddy Jurnali (International Journal of Business and Quality Research, 2025)
As the demand for sustainable practices in the manufacturing industry rises alongside global awareness of environmental and social impacts, this study explores the concept of ambidextrous sustainability. It emphasizes the significance of balancing sustainability exploration and exploitation to optimize overall sustainability performance. This research investigates how adopting ambidextrous sustainability effectively enables companies to harness existing resources while innovating for future sustainability. Furthermore, the study highlights the critical role of sustainability risk management as a moderating factor in this relationship. By understanding the dynamics between ambidextrous sustainability and risk management, companies can enhance their sustainability performance and address the challenges posed by evolving environmental regulations and market demands. The findings offer practical insights for organizations striving to incorporate sustainable practices into their operational strategies. Employing a quantitative approach with data collected from large and medium-sized manufacturing companies in the Riau Islands, Indonesia, the research reveals that companies adept at balancing sustainability initiatives are more likely to achieve long-term success and a competitive edge. In conclusion, this study contributes to the discourse on corporate sustainability by illustrating the interplay between strategic sustainability initiatives and risk management, ultimately guiding firms on their path toward sustainable development and improved performance in an increasingly eco-conscious world.